2019
DOI: 10.3390/plants8080270
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a Reference Genome in a Single Lab: The Possibility to Use Oxford Nanopore Technology

Abstract: The whole genome sequencing (WGS) has become a crucial tool in understanding genome structure and genetic variation. The MinION sequencing of Oxford Nanopore Technologies (ONT) is an excellent approach for performing WGS and it has advantages in comparison with other Next-Generation Sequencing (NGS): It is relatively inexpensive, portable, has simple library preparation, can be monitored in real-time, and has no theoretical limits on reading length. Sorghum bicolor (L.) Moench is diploid (2n = 2x = 20) with a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Remarkable exceptions to this role are sorghum, in whose genome only one STS gene has been identified [74,75], and grapevine, which possesses an uncommonly large number of STS genes. Both grapevine and sorghum genomes have been entirely sequenced [74,76]. Early Southern-blot analysis suggested that the grapevine STS gene family consisted of 15-20 members [77].…”
Section: Stilbene Synthasementioning
confidence: 99%
“…Remarkable exceptions to this role are sorghum, in whose genome only one STS gene has been identified [74,75], and grapevine, which possesses an uncommonly large number of STS genes. Both grapevine and sorghum genomes have been entirely sequenced [74,76]. Early Southern-blot analysis suggested that the grapevine STS gene family consisted of 15-20 members [77].…”
Section: Stilbene Synthasementioning
confidence: 99%
“…A total of 2 μg of genomic DNA was needed for nanopore sequencing ( Lee et al 2019 ). The genomic DNA was prepared using the NEB Next FFPE DNA Repair Mix kit (M6630, USA) and then processed with the ONT Template prep kit (SQK-LSK109, UK) following the manufacturer’s instructions ( Kim et al 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…While whole-genome Nanopore sequencing provides excellent resolution to potentially detect all TEIs in a genome, it is expensive when the genome is relatively large. For example, in our hands and based on previous reports using different species, it is challenging to generate more than 8 Gb of data per single MinION flow cell from plant material (Lee et al, 2019; Schalamun et al, 2019; Dmitriev et al, 2021). Obtaining only 4400 CANS reads (equivalent to 0.2× coverage of the A. thaliana genome) on a single flow cell, we were able to detect 86% of the genetically inherited EVD insertions.…”
Section: Discussionmentioning
confidence: 99%